2012
DOI: 10.5539/ijb.v4n4p66
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of DNA Barcoding for the Identification of Chenopodium murale L. (Chenopodiaceae)

Abstract: Chenopodium murale L. (Chenopodiaceae) is an erect annual herbaceous weed. This species is a threat for ecosystems worldwide as this annual-weed affects the growth and development of other plants by reducing the biological nitrogen-fixing ability. We evaluated the barcoding genes of the plastid region of C. murale [rbcL (Ribulose-1,5-bisphosphate carboxylase/oxygenase) and matK (Maturase K)] for the success of PCR amplification, the differential inter-specific divergences and the ability of a single gene or co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 31 publications
(31 reference statements)
1
6
0
Order By: Relevance
“…Consequently, the missing species in the database cannot be identified and the method may assign the query sequence to an incorrect species [25]. Similar result was previously reported on Chenopodium murale [26]. Their study reported that when using BLAST, the specimen was identified as Chenopodium murale for both matK and rbcL gene with 100% sequence similarity.…”
Section: Species Identificationsupporting
confidence: 73%
“…Consequently, the missing species in the database cannot be identified and the method may assign the query sequence to an incorrect species [25]. Similar result was previously reported on Chenopodium murale [26]. Their study reported that when using BLAST, the specimen was identified as Chenopodium murale for both matK and rbcL gene with 100% sequence similarity.…”
Section: Species Identificationsupporting
confidence: 73%
“…They concluded that rbcL sequences identified 92% of the samples at the genus level but only 17% at the species level. In another study, Bafeel et al (2012a) performed molecular characterization of Chenopodium murale , an invasive herbaceous weed species in Saudi Arabia with negative allelopathic effects to enhance the morphological identification system. Amplification of the barcoding genes rbcL and matK in C. murale’s plastid region indicated that matK possesses high discrimination efficiency and the lowest average pairwise sequence similarity in comparison to rbcL , as well as the fact that the combination of rbcL and matK could yield high resolutions.…”
Section: Plant Dna Barcoding: An Emerging Approachmentioning
confidence: 99%
“…There are several studies from Peninsular Arabia reporting the use of core barcode markers (rbcL and matK) (Figure 1), along with multi-locus markers for the identification and discrimination of plant taxa. For example, Al Qurainy et al [23][24][25][26][27] used supportive markers (ITS, rpoB, rpoC1, PSBA-trnH, and rps16) as well as the core DNA barcode markers (rbcL and matK) on SA plant resources. Bafeel et al [23][24][25] efficiently used rbcL and matK markers for studying arid plants.…”
Section: Introductionmentioning
confidence: 99%